PROBLEMS OF DIGITAL TRANSFORMATION OF THE RUSSIAN ECONOMY - V. Deryzemlya; A. Ter-Grigoryants (Вестник Северо-Кавказского федерального университета, 2022)
The article highlights and systematizes the features of the digital transformation of the Russian economy based on the organizational, legal, financial and technical and technological capabilities of business. Analytical data on the effectiveness of digitalization implementation in various sectors of the domestic economy are provided, which allow us to identify areas for improving the efficiency of their functioning. Based on the results of the research, the prospects for the development of the digital economy are formulated, and the main directions of the digital transformation strategy are described, which can be applied in the process of managing the economic processes of individual commercial structures.